Kwestionariusz Zaawansowania w Uważności (polska adaptacja i walidacja) - Radoń, Stanisław (Studia Psychologica: Theoria et praxis, 2022)
Objective: polish adaptation and validation of the 19-items MINDSES questionnaire (Observe, Nonreactivity, and Decentering) used to measure advancement in mindfulness practice among meditators and nonmeditators; examination of the associations between mindfulness advancement and mental health. Methods: two samples (N=882: females 79,2% and males 20,8%) aged 15-72 (M=37,07; SD=10,91) were used as follows: meditation advanced (N=656 – 74,6%: Christian meditation – 33,5%, mindfulness – 24,4%, and concentrative techniques i.e. yoga and Transcendental Meditation – 16,2%) and controlled toward the length of practice (under 1 year, 1-10 years, above 10 years), frequency of practices (from time to time, few times weekly, daily), health (healthy people, with physical problems, with mental health problems) and meditation naïve (N=226 – 25,4%). Results: 19 items Polish adaptation Mindfulness Advancement Questionnaire demonstrate the solid factor structure of the measurement (3-bifactor model), with high factor loadings, good composite (0,74≤CR≤0,93) and construct reliability (0,82≤H≤0,93), fine absolute stability (0,76≤rtt≤0,82), solid external validity, and measurement invariance. Conclusions: the validated questionnaire can be used as a valuable measure of mindfulness advancement in meditators, clinical and non-clinical populations, aged 15-72. Discussions focused on the role of the advancement of mindfulness practice on mental health.